2013
DOI: 10.1103/physrevb.88.125302
|View full text |Cite
|
Sign up to set email alerts
|

Role of the ligand layer for photoluminescence spectral diffusion of CdSe/ZnS nanoparticles

Abstract: The time-resolved photoluminescence (PL) characteristics of single CdSe/ZnS nanoparticles, embedded in a PMMA layer is studied at room temperature. We observe a strong spectral jitter of up to 55 meV, which is correlated with a change in the observed linewidth. We evaluate this correlation effect using a simple model, based on the quantum confined Stark effect induced by a diffusing charge in the vicinity of the nanoparticle. This allows us to derive a mean distance between the center of the particle and the d… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
36
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(37 citation statements)
references
References 30 publications
1
36
0
Order By: Relevance
“…While increasing the ZnS shell thickness can induce the photo-spectrum redshift owning to the increased size distribution in the samples with thicker ZnS shell (Baranov et al 2003;Zhu et al 2010). (Braam et al 2013) reported that spectral diffusion in photoluminescence is caused by diffusing charge in the ligand layer. The two influence factors can be explained by the larger blue shift fluctuation in the final stage of the process blue shift, that are shown by a larger error bar in the data.…”
Section: Discussionmentioning
confidence: 98%
“…While increasing the ZnS shell thickness can induce the photo-spectrum redshift owning to the increased size distribution in the samples with thicker ZnS shell (Baranov et al 2003;Zhu et al 2010). (Braam et al 2013) reported that spectral diffusion in photoluminescence is caused by diffusing charge in the ligand layer. The two influence factors can be explained by the larger blue shift fluctuation in the final stage of the process blue shift, that are shown by a larger error bar in the data.…”
Section: Discussionmentioning
confidence: 98%
“…S3)22. An optical microscope was used to identify suitable particles and to determine their diameters within an error margin of 0.2  μ m. The spheres were excited on the circumference by a diode laser (Linos model Nano 250) with a 405 nm wavelength with the power and spot size of 7  μ W and ~0.5  μ m, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…In this paper, we report that self-assembled π -conjugated polymer microspheres, without complicated fabrication processes and dye doping, exhibit WGM photoemission, as confirmed by means of the micro-photoluminescence ( μ -PL) technique22. The major challenge when studying WGM is the fabrication of well-defined, geometrically isotropic spheres.…”
mentioning
confidence: 86%
“…PL blinking, the term used for time-dependent digital jumps of the PL intensity between on and off emissivity states, has been attributed to the charging of the NCs or the activation of trapping processes in impurity states [10][11][12][13][14][15][16][17][18][19]. In contrast, SD, which is an unstable fluctuation of the PL transition energy, has been attributed to the quantum-confined Stark effect (QCSE) [6][7][8][9][20][21][22][23][24][25]. Since these PL profile fluctuations prevent us from developing stable, single-photon emitters for application in quantum communication and cryptography [26,27], the understanding and the control of those PL fluctuations is a central issue in the current research field.…”
Section: Introductionmentioning
confidence: 99%
“…This three-body excitonic complex often results in the formation of gray states with intermediate PL intensities, which appear during blinking [12][13][14][15][16][17][18][19]. On the contrary, when additional charges are located outside the NC, their Coulomb potential induces an electric field onto the crystal, which in turn causes a QCSE on the electron-hole pairs in the crystal and results in changes in the transition energies [9,[21][22][23][24]. Both charges inside and outside the NC affect the PL of single NCs, causing blinking and SD, and thus it is important to elucidate them for the deep understanding of the mechanisms of PL instabilities.…”
Section: Introductionmentioning
confidence: 99%